COMPREHENSIVE CARE ACCEPTANCE COMMITMENT THERAPY (ACT) IN CLIENTS WITH TYPE 2 DIABETES MELLITUS TOWARD COMPLIANCE AND HELPLESSNESS - Susila, Wahyu Dini Candra; Suroso, Heri; Fajriyah, Novita; Nurwahidah, Nurwahidah (SYNTHESIS Global Health Journal, 2023)
Background. Diabetes Mellitus (DM) is a health problem with an increasing prevalence and a high risk of serious and often fatal complications. DM is included in the group of metabolic disorders characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action, or both, one of which is a concern because it occurs due to dietary failure. Clients who have had diabetes for more than a year are almost entirely helpless. This study aim was to determine the benefits of acceptance and commitment therapy (hereinafter abbreviated as ACT) in resolving problems in clients with type 2 diabetes mellitus. Research Method. Case report on the implementation of ACT to reduce helplessness and increase dietary adherence. The subjects used were three clients with type 2 diabetes mellitus who experienced helplessness. In this case, implementation studies of three to four weeks with comprehensive care. Findings. The results of the study show that giving acceptance commitment therapy (ACT) can reduce helplessness and improve dietary compliance. Conclusion. ACT is recommended to improve dietary compliance and reduce the helplessness of DM clients.